VD_FINDINFO HC / 2012 / 535 vom 22. August 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, INDEMNITÉEN GÉNÉRAL, AVOCAT D'OFFICE | 109 al. 1 CPC (CH), 122 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)